Campylobacter coli cultured from the stools of a patient with immunoproliferative small intestinal disease. (20th February 2014) - Coeuret, S.; de La Blanchardière, A.; Saguet‐Rysanek, V.; Chèze, S.; Tavernier, M.; Arsène, D.; Criscuolo, A.; Brisse, S.; Vergnaud, M.; Verdon, R.; Lecuit, M.; Raoult, D.
Abstract Campylobacter has been associated with immunoproliferative small intestinal disease (IPSID), on the basis of 16S rDNA sequencing, in situ hybridization, and immunohistochemistry. Here, for the first time, we have cultured Campylobacter from the stools of a patient with IPSID. Phenotypic analysis and whole genome sequencing identified Campylobacter coli. PCR on a IPSID tissue biopsy sample was positive for Campylobacter coli and negative for Campylobacter jejuni. These findings further support a causative role for Campylobacter in the development of IPSID.